Gerromorpha (Hemiptera: Heteroptera) of eastern Mato Grosso State, Brazil: checklist, new records, and species distribution modeling - Dias-Silva, Karina; Moreira, Felipe Ferraz Figueiredo; Giehl, Nubia França Da Silva; Nóbrega, Caroline Correa; Cabette, Helena Soares Ramos (Zootaxa, 2013)
The infraorder Gerromorpha comprises semiaquatic bugs, most of which spend much of their lifetime on the water surface, between floating plants, or on the margins of water bodies. Based on literature and collections made on streams and lakes on municipalities of eastern Mato Grosso, Brazil, a list has been elaborated with 52 species, including several new records. Out of the recorded species, 26 belong to the family Veliidae, 20 to Gerridae, three to Hydrometridae, two to Mesoveliidae, and one to Hebridae. The modeling of the potential geographical distribution is also presented for the 20 species that have been recorded for the first time from the state.